Criminal Responsibility For Crimes Resulting From The Regional Head General Elections - Dewi Nabila Sya’bania; Rinaldy Amrullah; Satria Prayoga (LEGAL BRIEF, 2025)
Regional Head Elections are a fundamental manifestation of popular sovereignty at the regional level. They provide an arena for citizens to directly elect leaders who will determine the direction of regional policy. However, the implementation of Regional Head Elections in several regions is prone to fraud, which can undermine the democratic process itself. One relevant case, the focus of this research, is Decision Number 191/Pid.Sus/2024/PN.Met, involving Drs. Qomaru Zaman, M.A., Deputy Mayor of Metro City. The defendant delivered a statement that was deemed an invitation to the public to re-elect him. This case underscores the importance of effective law enforcement against violations committed by state officials in the implementation of regional elections. In this context, the role of the Prosecutor's Office becomes highly strategic as part of the Integrated Law Enforcement Center, working with the police and the Elections Supervisory Agency (Bawaslu). Criminal liability for the perpetrators of election-related crimes in this case has been applied in accordance with the principles of criminal law, specifically the principles of fault, capacity to be responsible, and legality.